Hairy root culture of Lactuca virosa L. - Anna Stojakowska; Janusz Malarz; Wanda Kisiel; Stanisław Kohlmünzer (Acta Societatis Botanicorum Poloniae, 2014)
A hairy root culture of Lactuca virosa L. (Asteraceae) was initiated by infection of the leaf explants of the aseptic plants with Agrobacterium rhizogenes - strain LBA 9402. One of the obtained clones which showed the most favourable growth rate was used for further investigation. An influence of different nutrient media and sucrose concentrations on the biomass accumulation was studied. The most advantageous for the biomass increment were media: MS and MS containing macronutrients reduced to half concentration, supplemented with 5% sucrose. A preliminary chromatographic analysis of the tissue extract revealed the presence of sesquiterpene lactones characteristic of the roots of the intact plant.